Upaya Guru dalam Menanamkan Rasa Hormat Siswa Melalui Pembelajaran Tematik di Kelas VB Sekolah Dasar Negeri 09 Kota Bengkulu (Studi Deskriptif) - Wartilia Desprananti; Pebrian Tarmizi (JURIDIKDAS, 2023)
This study aims to describe the efforts of teachers in instilling respect for students through Thematic learning in the VB class of State Elementary School 09, City of Bengkulu. This study uses a type of qualitative research and qualitative descriptive research methods. The research subjects were VB homeroom 09 Public Elementary School of Bengkulu City and the object of research was VB class students. The focus of research is the teacher's efforts to instill a respectful attitude towards students. Research instruments are researchers themselves (human instruments) with data collection techniques using observation, interviews, and documentation. The data obtained were analyzed through data reduction, data presentation, and drawing conclusions. Test the validity of the data through extension of observation, increase in perseverance and accuracy, and triangulation. The results of this study indicate that the researcher describes the efforts of the teacher in instilling respect for students by using attitudinal formation patterns, namely habituation and modeling (Thematic) through Thematic learning, such as teachers condition students not to chat during learning or discussion, the teacher exemplifies students not differentiate friends, and the teacher conditions and exemplifies to speak politely and behave politely. Based on the results of the study it can be concluded the efforts of VB homeroom teacher in instilling respect for students through Thematic learning in VB class of Public Elementary School 09 Kota Bengkulu: a) Treating other people with respect, b) Tolerating various differences, c) Using language and treatment polite, and d) Maintain and pay attention to the feelings of others.